2014
DOI: 10.1245/s10434-014-3866-4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Surgical Resection Following Imatinib Treatment in Patients with Recurrent or Metastatic Gastrointestinal Stromal Tumors: Results of Propensity Score Analyses

Abstract: Surgical resection of residual lesions after disease control with imatinib is likely to be beneficial to patients with recurrent or metastatic GISTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 24 publications
1
47
0
1
Order By: Relevance
“…Even in presence of peritoneal metastasis, considering surgery for primary along with oligo metastasis after anterior IM therapy should be considered. However, these are small numbers and the benefit of surgery in patients with metastatic GISTs still remains controversial (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Even in presence of peritoneal metastasis, considering surgery for primary along with oligo metastasis after anterior IM therapy should be considered. However, these are small numbers and the benefit of surgery in patients with metastatic GISTs still remains controversial (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that operative resection after imatinib therapy was beneficial for patients with recurrent/metastatic disease. 78 A more recent study 79 addresses the question regarding surgical removal of residual tumor after initial treatment with imatinib for metastatic GIST. The patients in the operative group (n = 42) were more likely to have a greater tumor burden than patients treated only with imatinib (n = 92); however, after appropriate statistical weighting and multivariable analysis, the surgical group had better outcomes for PFS (HR, 2.326; P = .0412) and OS (HR, 5.464; P = .0117), suggesting a role for metastectomy in patients with advanced GIST.…”
Section: The Role Of Metastasectomy In the Management Of Recurrent Gistmentioning
confidence: 99%
“…The Spanish group for research on sarcomas did a retrospective analysis of two cohorts with 171 patients and found that patients who had surgery after response or stable disease by imatinib had longer median OS than those who did not have surgery, 87 vs. 59 months [32 & ]. Also a Korean retrospective evaluation of 134 patients responding on imatinib treatment showed a significant benefit on progression-free survival and OS with surgery [33].…”
Section: Gastrointestinal Stromal Tumoursmentioning
confidence: 99%